Association of Sugar Intake with Inflammation- and Angiogenesis-Related Biomarkers in Newly Diagnosed Colorectal Cancer Patients. (28th May 2022) - Stewart, Kelly L.; Gigic, Biljana; Himbert, Caroline; Warby, Christy A.; Ose, Jennifer; Lin, Tengda; Schrotz-King, Petra; Boehm, Jürgen; Jordan, Kristine C.; Metos, Julie; Schneider, Martin; Figueiredo, Jane C.; et al.
Abstract: Evidence suggests a positive association between sugar intake and colorectal cancer (CRC) outcomes. We sought to investigate inflammation and angiogenesis as underlying mechanisms behind increased sugar intake and worse CRC outcomes. Pre-surgery serum samples were obtained from 191 patients diagnosed with primary invasive stage I-IV CRC. Biomarkers of inflammation (CRP, SAA, IL-6, IL-8, MCP-1, TNFα) and angiogenesis (VEGFA, VEGFD, sICAM-1 and sVCAM-1) were analyzed (Meso-Scale-Discovery). Fructose, glucose, sucrose, and total sugar intake (calories/day, % total calories) were assessed by FFQ. Pearson's correlation and multiple linear regression analyses were performed. Patients were on average 64 years old, 64% were male, the majority was diagnosed with stage II-III (58%) cancers, and 67% were either overweight or obese. Among normal-weight individuals (BMI <25 kg/m 2 ), we observed a significant inverse association between VEGFD and any type of sugar intake in cal/day (sucrose: p = 0.01, glucose and fructose: p < 0.001) and MCP-1 and fructose intake ( p = 0.05). The magnitude of reduction in VEGF ranged between −1.24 for sucrose to 4.49 for glucose intake, and −2.64 for fructose intake for MCP-1 levels. Sugar intake was associated with some inflammation or angiogenesis biomarkers, among CRC patients; differences were observed by adiposity that warrant further investigation. Supplemental data for this article is available online at at 10.1080/01635581.2021.1957133.